1964
DOI: 10.1098/rspb.1964.0017
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A and reproduction in rats

Abstract: Retinoic acid (vitamin A acid), the carboxylic acid corresponding to the primary alcohol retinol (vitamin A), has previously been thought to fulfil all the functions of vitamin A except in vision, since rats fed a diet deficient in retinol but supplemented with retinoic acid grow well, outwardly appearing healthy, yet become blind. This paper reports that female rats on such a diet had normal oestrous cycles and became pregnant when mated, but always resorbed the foetuses and no litters were born. The first ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
68
0
1

Year Published

1971
1971
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 326 publications
(70 citation statements)
references
References 35 publications
(17 reference statements)
1
68
0
1
Order By: Relevance
“…For instance, it has been proposed that RBP of Sertoli cell origin may facilitate the transport of ROL through the blood-tissue barrier (Shingleton et al, 1989), but whether RBP is actually expressed in the testis is uncertain (Soprano and Blaner, 1994). On the other hand, experiments conducted over the past decades in the rat have demonstrated that RA is instrumental to testicular physiology: VAD induces a rapid testicular degeneration characterized by a complete disappearance of all meiotic and postmeiotic germ cells (Howell et al, 1963;Thompson et al, 1964;van Pelt and de Rooij, 1990a;and references therein) and systemic administration of RA to vitamin A-deficient rats restores spermatogenesis from growth-arrested A spermatogonia (van Pelt and de Rooij, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it has been proposed that RBP of Sertoli cell origin may facilitate the transport of ROL through the blood-tissue barrier (Shingleton et al, 1989), but whether RBP is actually expressed in the testis is uncertain (Soprano and Blaner, 1994). On the other hand, experiments conducted over the past decades in the rat have demonstrated that RA is instrumental to testicular physiology: VAD induces a rapid testicular degeneration characterized by a complete disappearance of all meiotic and postmeiotic germ cells (Howell et al, 1963;Thompson et al, 1964;van Pelt and de Rooij, 1990a;and references therein) and systemic administration of RA to vitamin A-deficient rats restores spermatogenesis from growth-arrested A spermatogonia (van Pelt and de Rooij, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Retinol deficiency is associated with abnormal growth and development, keratinization of cutis and mucosa, lowered resistance to infection [26]. Also infertility is known to occur in cases of retinol deficiency in male and female [26]. It was reported that cellular-retinol binding protein and cellular-RA binding protein exist in the epithelial cells and stromal cells of the uterus, and that their expressions are regulated during menstrual cycle, estrus cycle and estrogen [27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…Retinol is required for normal growth and development in vertebrates animals. Retinol deficiency is associated with abnormal growth and development, keratinization of cutis and mucosa, lowered resistance to infection [26]. Also infertility is known to occur in cases of retinol deficiency in male and female [26].…”
Section: Discussionmentioning
confidence: 99%
“…However, it was found to be inactive in vision (Dowling & Wald, 1960) and reproduction (Thompson, Howell & Pitt, 1964). The conversion of retinal into retinol by retinal reductase (Futterman & Saslaw, 1961;Wald & Hubbard, 1949;Bliss, 1951) and the transformation of retinal into retinoic acid by retinal oxidase (Dmitrovskii, 1961;Futterman, 1962;Elder & Topper, 1962;Bamji, Mahadevan, Lakshmanan & Murthy, 1962) have both been demonstrated in liver and other tissues.…”
mentioning
confidence: 99%